Teachers navigating the diversified Swedish school market: lock-in and exclusion in the local labour market - Magnus Persson; Per Dannefjord (Education Inquiry)
This study examines the consequences that a highly diversified school market has on the teacher labour market. By interviewing 43 teachers in two different local school markets, one large and highly segregated and one smaller and less segregated, the teacher´s views and attitudes towards competing schools, different working conditions and educational ideas have been analysed. The results indicate that teachers in the more segregated school market compare their current workplace to others in terms of pupil composition. In the less segregated school market, there are small differences in terms of pupil composition, and the comparisons tend to focus on differences in organisational or educational ideas. The study shows that teachers are locked into various types of schools, where the diversity of the schools themselves is a consequence of the emerging diversification of the school market. The nature of the locking-in effects can be connected to the characteristics of the diversification in the local school market.